How New Public Management Drives Service Performance: The Mediating Roles of Servant Leadership and Leadership Behaviour Dimensions - Herman; Shofia Amin; Sigit Indrawijaya; Sry Rosita (Fundamental and Applied Management Journal, 2026)
New Public Management (NPM) has been widely adopted to improve public sector performance through efficiency, accountability, and performance-based management. However, the success of such reforms depends not only on managerial systems but also on leadership mechanisms that translate reform principles into service outcomes. This study aims to examine the effect of NPM on service performance through the mediating roles of servant leadership, task-oriented behaviour, relations-oriented behaviour, and change-oriented behaviour. This study employed a quantitative explanatory design using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 200 civil servants working in local government organizations in Jambi Province, Indonesia, through a structured questionnaire. The measurement and structural models were evaluated using SmartPLS 4.0. The findings show that NPM has a significant positive effect on servant leadership as well as on task-oriented, relations-oriented, and change-oriented behaviours. NPM also has a direct positive effect on service performance. Among the proposed mediators, only servant leadership has a significant positive effect on service performance and significantly mediates the relationship between NPM and service performance. In contrast, task-oriented, relations-oriented, and change-oriented behaviours do not show significant effects on service performance and do not mediate the relationship. These findings indicate that the effectiveness of NPM reforms is strongly influenced by value-based leadership rather than by behavioural dimensions alone. This study contributes to the public administration literature by offering a multidimensional mediation model and demonstrating that servant leadership is a more decisive mechanism in translating managerial reforms into improved service performance.